Pengembangan Bahan Ajar Menulis Cerpen dengan Teknik Parafrase pada Peserta Didik Kelas XI MAN 2 Samarinda - Nurhana; M. Siddik; A. Ridhani (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
The purposes of this research included: (1) developing teaching materials for writing short story using paraphrasing technique, (2) implementing learning to write short story using paraphrasing technique, (3) describing the feasibility of teaching materials for writing short story using paraphrasing technique. This research uses the research method of developing Willis's reflective, recursive, design, and development (R2D2) models. The method used is to produce a product and test the feasibility of the product in the form of teaching materials to write short stories with paraphrasing techniques in class XI MAN 2 Samarinda students. The results of the development of teaching materials for short story writing with paraphrasing techniques were validated by content/content experts who gave an average score of 92.04% and validation of teaching material experts obtained an average score of 95%. From the validation results the experts obtained an average score of 93.52% with a very good category. Thus, the teaching material produced is very suitable for use by students of class XI. Furthermore, implementing learning to write short stories with paraphrase techniques through planning assessments conducted by observer 1 who gave an average score of 80% and observer 2 gave an average score of 93.33%. The implementation of learning was given an average score of 81.73% by observer 1 and observer 2 giving an average score of 86.08%. From the average score given by observers 1 and 2 states learning takes place very well. The feasibility of teaching materials for short story writing with paraphrase techniques can be seen from the results of small group pretest trials with an average value of 67.8 and 86.7 posttests and field trials with an average value of 73.75 and posttests with an average value 88.18% with a very decent category.